El Nin~o and La Nin~a - Rose, Sally; Weather Channel (Television station : Atlanta, Ga.) (New York : Simon Spotlight, 1999)
Identifies the causes of the phenomena known as El Nin~o and La Nin~a, the differences between them, and why each causes such weather extremes.
At head of title: The Weather Channel.
Includes index.
Keywords: Climatic changes -- Juvenile literature; El Nin~o Current -- Juvenile literature; La Nin~a Current -- Juvenile literature; El Nin~o Current; La Nin~a Current